Production of Subjective Meanings and Bureaucratic Practices: Analysis of the Film La vida de los otros - Bravo, Omar Alejandro (Pensando Psicología, 2015)
Purpose: to address the question of bureaucracy, is subjective effects and its functional and structural relationship with certain social and institutional practices, a topic which is generally addressed in a fragmented manner from different areas of knowledge. Topic: The analysis of the film La vida de los otros facilitates an interpretation that links this phenomenon with forms of production of particular types of subjectivity, fundamentally characterized by their alienation in terms of the consequences and scopes of their praxis. At the same time, it is possible to reflect upon the ways in which the practices of the subjects themselves facilitate new venues for the production of subjective meanings. Development: The notions of subjective meaning, subjectivity and social subjectivity developed by Fernando González Rey constitute technical operators that facilitate this interpretive construction, take into consideration the interactions that occur among the protagonist of the film for this analysis. Conclusions: The analysis of the film shows the social and individual conditions for the production of new subjective meanings by the protagonists, while also facilitating reflection on the relationship between bureaucratic institutional practices and the forms of production of subjectivity.